Inflation Targeting in the United Kingdom : Information Content of Financial and Monetary Variables - Baumgartner, Josef (IMF Working Papers; Working Paper ;, 1996)
The main objective of this paper is to identify a set of leading indicators of inflation for the United Kingdom, and discuss the conceptual issues pertaining to inflation targeting. The main conclusions are that narrow money has strong leading indicator properties for inflation, while broad money does not. Long yields appear to have some information for the GDP deflator, and headline inflation, and short yields for underlying inflation. Spreads between commercial paper and gilts, and the yield curve, have very little predictive information on inflation. An interesting conclusion is that while the nominal effective exchange rate is not a good predictor of inflation, the sterling-deutsche mark exchange rate appears to have weak predictive information on the targeted measure of inflation.